Development of a hybrid heating system based on geothermal–photovoltaic energy to reduce the impact of frosts on inhabitants of rural areas in the ring of fire, southern Peru - Chavarria, Dana (2019)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.